2021
DOI: 10.1371/journal.pone.0245907
|View full text |Cite
|
Sign up to set email alerts
|

Converting the maybes: Crucial for a successful COVID-19 vaccination strategy

Abstract: Background Broad community acceptance of a COVID-19 vaccination will be critical for effectively halting the spread of the virus. In this study, we focus on factors that differentiate those who are undecided from those who are either willing or unwilling to accept a prospective COVID-19 vaccine. Methods An online survey in May 2020 assessed Australian adults’ willingness to receive a COVID-19 vaccine (yes, maybe, no). A multinomial logistical regression of responses (N = 1,313) was used to identify correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 11 publications
2
58
0
2
Order By: Relevance
“… 31 However, in our study, the ‘unsure’ group is twice the size of the ‘non-uptake’ group. An Australian study by Attwell et al 32 demonstrated that respondents were more likely to be in the ‘maybe’ group versus the ‘no’ group for vaccination if they perceived COVID-19 to be a severe disease and not a ‘hoax’, were more likely to have the influenza vaccination and had greater trust in science. In the case of our study, the ‘unsure’ group, which makes a significant portion of the ‘non-uptake’ group, may change their mind about the vaccine once further details on an approved vaccine become available, particularly information on safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“… 31 However, in our study, the ‘unsure’ group is twice the size of the ‘non-uptake’ group. An Australian study by Attwell et al 32 demonstrated that respondents were more likely to be in the ‘maybe’ group versus the ‘no’ group for vaccination if they perceived COVID-19 to be a severe disease and not a ‘hoax’, were more likely to have the influenza vaccination and had greater trust in science. In the case of our study, the ‘unsure’ group, which makes a significant portion of the ‘non-uptake’ group, may change their mind about the vaccine once further details on an approved vaccine become available, particularly information on safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid, large-scale uptake of vaccines against COVID-19 is required to control and eventually end the current pandemic. However, vaccine hesitancy may prevent a significant share of the population from getting vaccinated (Attwell et al, 2021). Previous research indicates that low vaccination intentions can result from people having little confidence in vaccine safety, being complacent (i.e., considering vaccination as rather unnecessary) or calculative (i.e., extensively weighing risks and benefits), encountering barriers constraining vaccination, or perceiving low collective responsibility (e.g., lack of willingness to get vaccinated to protect others) (Betsch et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…14 Studies conducted between April and June 2020 found between 65% and 86% of Australians were likely to accept the COVID-19 vaccine. [15][16][17] The WHO listed 'vaccine hesitancy' as one of the top threats to global health in 2019, 18 even before the pandemic. Hence, implementing an evidence-based plan for COVID-19 vaccine roll-out is crucial.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%